Pengaruh Digital Marketing, Kualitas Pelayanan, Dan Penampilan Produk Terhadap Keputusan Pembelian (Studi Kasus Es Teler Sempet Sayang) - Kafi, Jamaludin; Wahono, Budi; Wahyuningtyas, Nanik (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine the influence of Digital Marketing, Service On Quality, and Product Apperance on Purchasing Decisions. The sample for this research is Es Teler Sempet Sayang consumers to collect data using a quitionaire. To analyze the data sing the validity test, Reliability test, Normality test, Classic Assumtions test, Multiple Linier Regrssion Analysis, F statistical test and t statical test, Cofficient of Determination Test using IBM Statistics SPSS 25From of the result calculation using SPSS, namely the Digital Marketing variables, Service Quality and Product Appearance, have a simultancous influence on purchasing decisions. Meanwhile, partialy Digital Marketing, Service Quality, and Product Appearnce have and influence on Purchasing Decisions Keywords : Digital Marketing, Service Quality, Product Appearance, and Purchasing Decisons.